Proceedings of the 4th Workshop on Argument Mining 2017
DOI: 10.18653/v1/w17-5109
|View full text |Cite
|
Sign up to set email alerts
|

Manual Identification of Arguments with Implicit Conclusions Using Semantic Rules for Argument Mining

Abstract: This paper describes a pilot study to evaluate human analysts' ability to identify the argumentation scheme and premises of an argument having an implicit conclusion. In preparation for the study, argumentation scheme definitions were crafted for genetics research articles. The schemes were defined in semantic terms, following our proposal to use semantic rules to mine arguments in that literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…First, the schemes in the catalogue have not been rigorously evaluated for inter-annotator agreement. However, a previous study (Green, 2017) suggested that some of the schemes, such as Agreement, as well as implicit conclusions of arguments, could be consistently identified. The current catalogue improves upon the materials used in our previous study.…”
Section: Resultsmentioning
confidence: 95%
“…First, the schemes in the catalogue have not been rigorously evaluated for inter-annotator agreement. However, a previous study (Green, 2017) suggested that some of the schemes, such as Agreement, as well as implicit conclusions of arguments, could be consistently identified. The current catalogue improves upon the materials used in our previous study.…”
Section: Resultsmentioning
confidence: 95%
“…Rather than annotate a scientific corpus at the text level, in [12] we propose creation of a semantically annotated corpus of arguments in a partially automated, two-step process. The first step would be to identify the entities and relations in the text.…”
Section: Discussionmentioning
confidence: 99%
“…implemented in the logic programs. Then another small study was done to see if, given the revised catalog and excerpts of the CRAFT article containing arguments with implicit conclusions, other researchers could reliably identify the premises and argumentation scheme for five types of argument [12]. Although mainly successful, the study revealed some confusion between schemes such as Analogy and Consistent Explanation, pointing to the need to better explain those schemes in a catalog for use by human annotators.…”
Section: Argumentation Schemesmentioning
confidence: 99%
“…Green in [26] provided an argument action method and inter-argument relations for the annotation of arguments in study papers. In one of a few researches that presented in an argument concert on the biomedical filed.…”
Section: Toulmin's Model In Medicinementioning
confidence: 99%